Alcohol and Group Formation - Sayette, Michael A.; Creswell, Kasey G.; Dimoff, John D.; Fairbairn, Catharine E.; Cohn, Jeffrey F.; Heckman, Bryan W.; Kirchner, Thomas R.; Levine, John M.; Moreland, Richard L. (Psychological Science, 2012)
We integrated research on emotion and on small groups to address a fundamental and enduring question facing alcohol researchers: What are the specific mechanisms that underlie the reinforcing effects of drinking? In one of the largest alcohol-administration studies yet conducted, we employed a novel group-formation paradigm to evaluate the socioemotional effects of alcohol. Seven hundred twenty social drinkers (360 male, 360 female) were assembled into groups of 3 unacquainted persons each and given a moderate dose of an alcoholic, placebo, or control beverage, which they consumed over 36 min. These groups’ social interactions were video recorded, and the duration and sequence of interaction partners’ facial and speech behaviors were systematically coded (e.g., using the Facial Action Coding System). Alcohol consumption enhanced individual- and group-level behaviors associated with positive affect, reduced individual-level behaviors associated with negative affect, and elevated self-reported bonding. Our results indicate that alcohol facilitates bonding during group formation. Assessing nonverbal responses in social contexts offers new directions for evaluating the effects of alcohol.